A Study of the Impact of Social Capital on Job Satisfaction: The Mediating and Moderating Role of Social Trust and Academic Leadership - Mondal, Sourav; Sharma, Adya; Panackal, Nehajoan (Prabandhan: Indian Journal of Management, 2025)
Purpose : Social capital represents the formal and informal network of relationships across all organizational levels. Existing research on job satisfaction profoundly highlights pay, working conditions, and work relations as key contributors. The current study aimed to study the impact of social capital on job satisfaction through the mediating and moderating role of social trust and academic leadership. Methodology : This study utilized partial least squares structural equation modeling (PLS-SEM) for data analysis, given its suitability for studies with exploratory objectives and a focus on prediction. Findings : The study showed that organizational justice, social structure, and commitment partially mediated with job satisfaction. The analysis also showed that social cohesion was entirely mediation, which implied that without academic leadership, the direct effect of social cohesion on job satisfaction would be negligible or non-existent. Practical Implications : The study aimed to contribute to organizational behavior and educational management theories. The study findings prompted academicians and policymakers to improve job satisfaction by fostering social capital, trust, and leadership in academic settings. The study could offer insights for universities or organizations to enhance employee job satisfaction by leveraging social capital. Originality : The study is unique, as numerous studies have independently focused on job satisfaction and social capital. This study attempted to examine job satisfaction from the perspective of social capital.